Surgical site infections after pancreatic surgery in the era of enhanced recovery protocols - Joliat, Gaëtan-Romain (Medicine (Baltimore), 2018)
Few data exist on risk factors (RF) for surgical site infections (SSI) among patients treated in an enhanced recovery after surgery (ERAS) pathway. This study aimed to assess RF for SSI after pancreas surgery in a non-ERAS group and an ERAS cohort. An exploratory retrospective analysis of all pancreas surgeries prospectively collected (01/2000–12/2015) was performed. RF for SSI were calculated using uni- and multivariable binary logistic regressions in non-ERAS and ERAS patients. Pancreas surgery was performed in 549 patients. Among them, 144 presented a SSI (26%). In the non-ERAS group (n = 377), SSI incidence was 27% (99/377), and RF for SSI were male gender and preoperative biliary stenting. Since 2012, 172 consecutive patients were managed within an ERAS pathway. Forty-five patients (26%) had SSI. On multivariable analysis no RF for SSI in the ERAS cohort was found. In the ERAS group, patients with a pathway compliance ≤70% had higher occurrence of SSI (30/45 = 67% vs. 7/127 = 6%, p < 0.001) and patients with and without SSI had similar median overall compliances (77%, IQR 71–80 vs. 80%, IQR 73–83, p = 0.097). In the non-ERAS cohort, male gender and preoperative biliary stenting were RF for SSI, whereas in the ERAS group no RF for SSI was found. In an ERAS pathway, having an overall compliance >70% might diminish the SSI rate.